Income generation through rehabilitation of imperata grasslands: production of vitex pubescens as a source of charcoal - Utama, R.; Rantan, D.; Jong, W. de; Budhi, G.S. (1999)
We have presented a tree-planting technology that may allow reclaiming Imperata cylindrica grassland and at the same time increase incomes for local swidden agriculturist in West Kalimantan. It is expected that this technology allows us to draw some general conclusions about what should be considered as the domestication of tree species. Domestication of a trees species should be largely concerned with providing the technology that allows the tree-planting agents to successfully cultivate the tree species, meaning that the tree species can successfully be reproduced and lead to achieving an economic profit. Developing the technology has many facets. What these facets are depends both on the characteristics of the tree species and the opportunities and constrainsts of the tree planting agent. Selection of certain genetic strains may be one facet of the domestication, but, as the case described here demonstrates, it is not always a necessary requirement